2010
DOI: 10.1007/s10948-010-1087-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Electronic Properties of Nitrogen-Doped Lanthanum Sesquioxide La2O3 as Predicted from First Principles

Abstract: Using the ab initio FLAPW-GGA method we examine the electronic and magnetic properties of nitrogen-doped nonmagnetic sesquioxide La 2 O 3 emphasizing the role of doping sites in the occurrence of d 0magnetism. We predict the magnetization of La 2 O 3 induced by nitrogen impurity in both octahedral and tetrahedral sites of the oxygen sublattice. The most interesting results are that (i) the total magnetic moments (about 1 μ B per supercells) are independent of the doping site, whereas (ii) the electronic spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The interaction between ions and valence electrons was described by the projected additive wave (PAW) method, and the exchange-correlation potential between electrons was processed by the Perdew-Burke-Ernzerhof (PBE) functional of generalized gradient approximation (GGA). 29,32,33 Through testing, the plane wave truncation kinetic energy was set as 600 eV, the force was distributed to each atom, and the convergence value of the total system energy was less than 3.0 × 10 −3 eV nm −1 and 1.0 × 10 −5 eV per atom, respectively. The deviations of stress and displacement were less than 0.05 GPa and 1.0 × 10 −4 nm, respectively.…”
Section: Calculating Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between ions and valence electrons was described by the projected additive wave (PAW) method, and the exchange-correlation potential between electrons was processed by the Perdew-Burke-Ernzerhof (PBE) functional of generalized gradient approximation (GGA). 29,32,33 Through testing, the plane wave truncation kinetic energy was set as 600 eV, the force was distributed to each atom, and the convergence value of the total system energy was less than 3.0 × 10 −3 eV nm −1 and 1.0 × 10 −5 eV per atom, respectively. The deviations of stress and displacement were less than 0.05 GPa and 1.0 × 10 −4 nm, respectively.…”
Section: Calculating Methodsmentioning
confidence: 99%
“…The result indicated that Sr-doped La 2 O 3 clusters had higher thermodynamic and kinetic activity due to the catalytic oxidative coupling of methane, wherein the formed Sr–O bond had stronger reactivity with methane and a lower energy barrier to overcome the reaction with methane than the La–O bond. Bannikov et al 29 reported that the bonding of the doped elements had a significant impact on the magnetic properties of La 2 O 3 . The nitrogen (N)-doped La 2 O 3 combined with six ligands had magnetic, narrow-band semiconductor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…5 N impurities at anionic sites (oxygens) present a splitting of their p-bands and the majority-spin states are completely occupied while the minority-spin states are partially occupied leading to half-metallicity. [17][18][19][20][21][22] Experimental evidence for the occurrence of magnetism in N-doped MgO has been provided by Liu and collaborators. 23 An alternative way to half-metallic sp-electron ferromagnets is the growth of I/II-IV/V nanostructures in metastable lattice structures similar to the case of transition-metal pnictides and chalcogenides in the metastable zincblende structure.…”
Section: Introductionmentioning
confidence: 99%